PENGGUNAAN GAMIFICATION BERBASIS TEKNOLOGI TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Nurul Musabbikhati; Reza Rachmadtullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low ability of students to think creatively in the learning process. One effort to improve this ability is to apply an interesting and fun learning method, namely the technology-based gamification method. This research aims to determine the effect of applying the gamification method on students' creative thinking abilities in Pancasila Education lessons in class IV elementary school. This research uses a quantitative approach with an experimental type of research, using a one group pretest-posttest design. The research subjects were 28 students in class IV-B at SDN Sumur Welut III/440 Surabaya. Data was collected through pretest and posttest instruments to measure students' creative thinking abilities before and after being given treatment in the form of a gamification method. The research results showed that there was a significant increase in students' creative thinking abilities after implementing the technology-based gamification method. This proves that the gamification method is not only effective in creating a pleasant learning atmosphere, but is also able to encourage students to think more creatively in understanding Pancasila Education material. Thus, this method can be an innovative learning alternative to improve the quality of education, especially in developing students' creative thinking skills at the elementary school level.